2020
DOI: 10.1080/13540602.2020.1719059
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of teachers’ subjective wellbeing: understanding the links between teachers’ income satisfaction, altruism, self-efficacy and work satisfaction

Abstract: This article examines the nature of teachers' subjective wellbeing. Drawing upon the survey evidence from a three-year mixed methods study in China, the article explores the dynamic interaction between key aspects of teachers' subjective wellbeing: altruism and self-efficacy (psychological functioning) and work satisfaction and income satisfaction (cognitive dimension). The results show that although teachers' judgement of the quality of life in their workplaces reflects the strengths of their altruistic value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 88 publications
0
32
0
3
Order By: Relevance
“…The TAs all suggested that teachers should foster students' interest in learning Chinese, rather than imparting knowledge to students through lecturing. Such findings also resonated with altruistic motivations, such as caring for students' growth and development [45,46]. Despite the similarities, an interesting difference revealed from the data was that Mindy, as a major-consistent TA, had the least number of expectancies serving as motivations for her professional sustainability, in comparison with either Wendy (a major-unrelated TA) or Sally (a major-switched TA).…”
Section: Discussionmentioning
confidence: 74%
“…The TAs all suggested that teachers should foster students' interest in learning Chinese, rather than imparting knowledge to students through lecturing. Such findings also resonated with altruistic motivations, such as caring for students' growth and development [45,46]. Despite the similarities, an interesting difference revealed from the data was that Mindy, as a major-consistent TA, had the least number of expectancies serving as motivations for her professional sustainability, in comparison with either Wendy (a major-unrelated TA) or Sally (a major-switched TA).…”
Section: Discussionmentioning
confidence: 74%
“…The complex relationship between money and subjective well-being has been studied by scholars in different social and economic theories (Song et al, 2020). For example, Veenhove's absolute theory assumes a relationship between satisfaction of basic needs and subjective well-being, which is indicated by the threshold income level, where if income exceeds the threshold level, the effect of rising income becomes trivial (Clark & Oswald, 1996;Easterlin, 1995;Oswald, 1997;Veenhoven, 1991).…”
Section: Teacher Income Satisfactionmentioning
confidence: 99%
“…There are many social and economic evidences on the basic threshold and relative effects of income that have contributed to the discussion of the importance of monetary incentives in the recruitment and retention of teachers (Song et al, 2020). Some research found that the high salary of teachers is positively related to the length of their working years (Borman & Dowling, 2008;Dolton & Klaauw, 1995;Hanushek et al, 2004;Loeb & Luczak, 2013;Macdonald, 1999;Murnane & Olsen, 1990;Rivkin et al, 2005).…”
Section: Teacher Income Satisfactionmentioning
confidence: 99%
“…The known concepts of subjective well-being are based on the use of various indicators that reflect feelings, opinions, or perceptions of respondents (Fitch et al, 2017;Song et al, 2020). These concepts are oriented on perceiving the very phenomenon of subjective well-being and the factors that determine it.…”
Section: Problem Statementmentioning
confidence: 99%
“…It is also a factor of the success of adaptation to the professional environment, and a condition necessary for high results in work. When defining the concept of "subjective well-being", researchers consider that it is an integral psychological characteristic of a person's life and reflects the value basis of his attitude to various spheres of his own life and activity, as well as the level of adaptation to them (Zenina, 2012). Recognizing the systematicity and integrity of such a characteristic as subjective well-being, the authors of this research believe that the measure of its presence may differ in different constituents of human life.…”
Section: Introductionmentioning
confidence: 99%